Inflammation and Retinal Disease: Complement Biology and Pathology - Lambris, John D.; Adamis, Anthony P.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2010)
Numerous studies have pointed to the key role of complement in the pathogenesis of retinal disease, particularly age-related macular degeneration (AMD). Reports about new gene associations and links to other physiological pathways are emerging almost on a weekly base. Several promising clinical candidates covering a wide area of potential treatment applications are in the pipelines of both industrial and academic groups. This indicates an increasing interest in complement as a therapeutic target. In view of these exciting discoveries, scientists from around the world convened at the 1st Aegean Conferences Conference on Inflammation and Retinal Disease: Complement Biology and Pathology (June 10-17, 2007) in Crete, Greece, to discuss recent advances in this rapidly-evolving field. This volume represents a collection of topics on the functions of complement in eye diseases, pathophysiology, protein structures, and complement therapeutics discussed during the conference.
The Case for Complement and Inflammation in AMD: Open Questions -- The Role of Complement in AMD -- Multiple Interactions of Complement Factor H with Its Ligands in Solution: A Progress Report -- Genetic Control of Complement Activation in Humans and Age Related Macular Degeneration -- Bisretinoids of RPE Lipofuscin: Trigger for Complement Activation in Age-Related Macular Degeneration -- The Role of the Classical Complement Cascade in Synapse Loss During Development and Glaucoma -- A Role for Complement in Glaucoma? -- The ATP-Binding Cassette Transporter ABCA4: Structural and Functional Properties and Role in Retinal Disease -- Suppression of Drusen Formation by Compstatin, a Peptide Inhibitor of Complement C3 activation, on Cynomolgus Monkey with Early-Onset Macular Degeneration -- A Targeted Inhibitor of the Complement Alternative Pathway Reduces RPE Injury and Angiogenesis in Models of Age-Related Macular Degeneration -- Complement Depletion with Humanized Cobra Venom Factor in a Mouse Model of Age-Related Macular Degeneration.
Keywords: Medicine; Ophthalmology; Medicine & Public Health; Ophthalmology